The exercise pill: should we replace exercise with pharmaceutical means?. Issue 1 (2nd January 2017) - Loland, Sigmund
Abstract: New physiological and pharmacological research points to the possibility of a pill that produces the complete physiological effects of exercise. Is replacement of exercise with a pill a good idea? And if so, under what circumstances? To explore answers, I have examined three approaches to the understanding exercise. From a dualist point of view, exercise is explained mechanistically in terms of physiological cause and effect relationships. From this perspective, and in particular for reluctant exercisers, there seems to be no strong argument against the use of a pill. From a phenomenological point of view, exercise is understood from a first person perspective focusing on experiential qualities. It is argued that a pill can never replace the embodied, experiential values of exercising and their potential ethical significance. In other words, the use of a pill is rejected. From a critical social constructivist point of view, exercise is understood as an expression of sociocultural values. Exercise can be a source of both bodily alienation and embodied self-realization and meaning. It is argued that in settings of alienating exercise malpractice, an exercise pill can be a temporary lesser evil approach. It is pointed out, however, that the long-term solution to malpractice is not a pill but a change of practice. In a final section, the possibility of the exercise pill is contextualized in the larger, bio-ethical debate on human enhancement.